Can Aquatic Bacteria Save The Planet? A Review of Gene Expression Technologies Associated with the Degradation of Plastic Polymers / Review Article - Muna Mohammed Khayri; Hiba Naser Ali Alsahoo; Abdalkader Saeed Latif; Reyam Naji Ajmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The global environmental crisis caused by plastic pollution has intensified in recent years, particularly in aquatic ecosystems such as rivers, lakes, and oceans, creating an urgent need for effective and sustainable solutions. This article explores the potential role of aquatic bacteria in degrading plastic polymers by reviewing the biological and molecular mechanisms these microorganisms use to break down complex synthetic materials. Special attention is given to key genes and enzymes involved in plastic degradation, including PETase and MHETase, which play a critical role in the decomposition of polyethylene terephthalate (PET). In addition, the article highlights advanced gene expression and analysis techniques, such as metagenomics, transcriptomics, and proteomics, to better understand bacterial activity and degradation dynamics in natural environments. The main problem addressed is the continuous and unsustainable production and consumption of plastics, which has resulted in extensive pollution of freshwater and marine systems, while conventional waste treatment methods remain largely ineffective. The objective of this article is to provide a comprehensive scientific review of biotechnological approaches used to analyze and utilize aquatic bacteria for plastic degradation, focusing on molecular aspects and environmental applications. Using a literature review method, studies published between 2018 and 2024 were analyzed to evaluate effective bacterial models, technological challenges, and future prospects. The findings indicate that aquatic bacteria offer promising potential as biological tools for mitigating plastic pollution through sustainable environmental strategies.